Inteligência emocional: fatores influenciadores e impacto nos enfermeiros em cuidados intensivos - Encarnação, Rúben Miguel Câmara (2018)
Objective: to analyze the evidence on the factors that influence the emotional intelligence of intensive care nurses. Methods: systematic review of the literature. We used the databases CINAHL Complete, Academic Search Complete, MedicLatina, Psychology and Behavioral Sciences Collection, MedLine with Full Text (via EBSCO HOST), MedLine Complete (via PubMed), SCOPUS and other sources, such as Google Scholar, clinical trial registration sites and manual/cross-references search. A total of 1,307 articles were published until April 2018, and nine were included in the study. Results: the factors that influenced nurses’ emotional intelligence were age, sex, emotional experience, training and personality; and the impact of emotional intelligence was translated on a personal, professional and caring level. Conclusion: the practice of nursing in intensive care units is influenced by the nurse’s emotional intelligence. This intelligence is affected by several factors and, because it is learned, must be stimulated in formative contexts.